2018
DOI: 10.1039/c8sm01178h
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical properties of monodomain nematic main-chain liquid crystal elastomers

Abstract: Two-stage thiol-acrylate Michael addition reactions have proven useful in programming main-chain liquid crystal elastomers (LCEs). However, the influence of excess acrylate concentration, which is critical to monodomain programming, has not previously been examined with respect to thermomechanical properties in these two-stage LCEs. Previous studies of thiol-acrylate LCEs have focused on polydomain LCEs and/or variation of thiol crosslinking monomers or linear thiol monomers. This study guides the design of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 58 publications
5
70
0
Order By: Relevance
“…Control of LCE properties, such as transition temperatures and actuation strain, can be achieved by varying the thiol chain extender, crosslinker, and/or mesogen concentration . We first varied the crosslinker concentration within the inks (0.1, 0.2, 0.4, and 0.6 molar ratio) (Table S1, Supporting Information) while maintaining EDDT as the chain extender and RM82 as the mesogen.…”
Section: Resultsmentioning
confidence: 99%
“…Control of LCE properties, such as transition temperatures and actuation strain, can be achieved by varying the thiol chain extender, crosslinker, and/or mesogen concentration . We first varied the crosslinker concentration within the inks (0.1, 0.2, 0.4, and 0.6 molar ratio) (Table S1, Supporting Information) while maintaining EDDT as the chain extender and RM82 as the mesogen.…”
Section: Resultsmentioning
confidence: 99%
“…A two-stage Michael Addition and Photopolymerization scheme was applied to fabricate the LCE (Figure 1), as described in previous studies. 3,27 The constituent F I G U R E 1 (a) Schematic of the chemicals used in the fabrication of LCE. A two-stage fabrication scheme was employed -first Michael Addition reaction, followed by a radical Photopolymerization reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, for potential biomedically-related applications, the nematic-isotropic transition temperature is typically upwards from 70 C. 27,28 Recently, only a few researchers have reported LCEs that undergo nematicisotropic transition at a lower temperature. 16,28 Inoue et al fabricated a novel LCE system that shifts diffusivity, rather than shape, at body temperature.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in good agreement with the DSC results. Furthermore, the tan δ peak values were approximately 1.6 times greater than those of the LCEs with a high crosslink density, which implies that these samples have higher damping capabilities compared with the LCEs having a higher crosslink density [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, extensive studies on LCE synthesis have been reported based on diacrylate-, divinyl-, or diglycidyl-functionalized LC monomers (so-called reactive mesogens). These monomers can first be chain-extended using alkyl dithiols [19][20][21][22][23][24][25][26][27][28], alkyl amines [29][30][31], or alkyl dicarboxylic acids [32,33], and then they can be crosslinked in the presence or absence of multifunctional crosslinkers to obtain main-chain LCEs. One of the major advantages of the above-mentioned method is that various LC alignment methods can be integrated during LCE synthesis.…”
Section: Introductionmentioning
confidence: 99%